2013
DOI: 10.1155/2013/946432
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Exercise and Chronic Exercise on the Liver Leptin-AMPK-ACC Signaling Pathway in Rats with Type 2 Diabetes

Abstract: Aim. To investigate the effects of acute and chronic exercise on glucose and lipid metabolism in liver of rats with type 2 diabetes caused by a high fat diet and low dose streptozotocin (STZ). Methods. Animals were classified into control (CON), diabetes (DC), diabetic chronic exercise (DCE), and diabetic acute exercise (DAE) groups. Results. Compared to CON, the leptin levels in serum and liver and ACC phosphorylation were significantly higher in DC, but the levels of liver leptin receptor, AMPKα1/2, AMPKα1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 52 publications
5
20
1
Order By: Relevance
“…(237^9 mg/dl) [19], and Otsuko LongEvans Tokushima Fatty (222^6 mg/dl) rat models [20]. The study also showed that in agreement with earlier studies [13], placement of Plexiglass clips on renal arteries led to renal hypertension 4 weeks after the operation.…”
Section: Isolated Aortic Studysupporting
confidence: 87%
“…(237^9 mg/dl) [19], and Otsuko LongEvans Tokushima Fatty (222^6 mg/dl) rat models [20]. The study also showed that in agreement with earlier studies [13], placement of Plexiglass clips on renal arteries led to renal hypertension 4 weeks after the operation.…”
Section: Isolated Aortic Studysupporting
confidence: 87%
“…These data suggest that a single bout of exercise does not affect hepatic gluconeogenesis either in mice fed with CD or HFD. This is in contrast with results from other studies in rodents . Knudsen et al .…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, they observed that phosphorylation of ACC and AMPK decreased immediately after exercise, suggesting that β‐oxidation is not a major contributor to energy production in the liver. This is in agreement with another recent study showing decreased AMPK phosphorylation in rat liver in response to acute exercise . As it is clear that proteins show a differential expression according the intensity of exercise, the time elapsed after exercise, and the presence of diabetes, we speculate that the intensity of our exercise bout was insufficient to induce a transcriptional response in non‐insulin resistant mice.…”
Section: Discussionsupporting
confidence: 93%
“…Zhao et al (2011) demonstrated improvements in hypothalamic leptin signaling in rats submitted to chronic exercise. In the same line of thought, Yi et al (2013) showed an increase in leptin receptors on liver and vascular smooth muscle. Other studies proposed mechanisms related with reduction on fat pad mass (Estadella et al, 2004;Park et al, 2012).…”
Section: Discussionmentioning
confidence: 69%